Safe third countries : extending the EU asylum and immigration policies to Central and Eastern Europe - Lavenex, Sandra (Budapest ; New York : CEU Press, 1999)
"At a time when many transition countries are trying to enter the European Union, Lavenex highlights the willingness of Central and East European countries to adopt Western European policies aimed at fighting illegal immigration and reducing the numbers of asylum seekers as a political bargaining tool in exchange for future membership in the EU. She also argues that the emergent European refugee regime undermines the values of international refugee protection and diffuses states' responsibilities by establishing a system of negative redistribution for the handling of asylum claims."--Jacket
1. Refugees and International Relations -- 2. The Emergence of the EU Refugee Regime -- 3. The Extension of the EU Refugee Regime -- 4. Central and Eastern Europe's Adaptation to the EU 'Acquis' -- 5. A Clash of Regimes? European versus International Refugee Protection.
Includes bibliographical references (pages 177-184) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: European Union -- Europe, Eastern; European Union; Asylum, Right of -- European Union countries; Refugees -- Legal status, laws, etc. -- European Union countries; Asylum, Right of -- Europe, Eastern; Refugees -- Legal status, laws, etc. -- Europe, Eastern; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Asylum, Right of; Refugees -- Legal status, laws, etc; Eastern Europe; European Union countries